Professional Values of Undergraduate Students at a Nursing School in South Africa - Portia Bimray; Jennifer Chipps; Victoire Ticha (Nursing Research and Practice)
Background. Nursing schools play an important role in instilling nursing professional values in undergraduate nursing students and ensuring that they produce professional nurse graduates. Several studies in various countries have been conducted to describe the professional values held by nursing students, but this has not been explored in detail in South Africa. Aim. The purpose of this study was to describe the professional values held by undergraduate degree students at a nursing school in South Africa. Methods. A cross-sectional survey using a self-administered questionnaire was conducted. With a population of 1,233 undergraduate nursing students across four years in the degree programme at the nursing school, a sample of 294 was calculated as the representative (95% CI, 5% error, and 50% response distribution). The 26-item nurses professional values scale revision (NPVS-R) with five value dimensions was used to collect the data. Means, frequencies, and confidence intervals were used to describe the values and Mann–Whitney U tests and Kruskal–Wallis independent sample tests were used to compare the findings with the demographic characteristics. Results. A total number of 245 respondents completed the questionnaire (response rate of 83.3%). Overall, the nurse professional value score was high (113.1 ± 13.1). The values of trust (4.46 ± 0.61), justice (4.39 ± 0.57), and caring (4.38 ± 0.55) were rated significantly higher than those of professionalism (4.23 ± 0.64) and activism (4.22 ± 0.57). First- and final-year students had significantly higher professional value scores. Conclusion. The study results describe the professional values of undergraduate nursing students in the school and confirmed the importance of trust, justice, and caring as the key professional values in the South African setting. Clinical Relevance. Nursing education should embed and monitor nursing professional values in the curriculum. Instilling nursing professional values in undergraduate nurses during formal training programmes improves quality patient care and service delivery for clinical practice.